The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s00127-006-0130-7
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in three generations of Iranian medical students and doctors

Abstract: This study suggests that psychological morbidity was common in Iranian medical students and practitioners, particularly women. Women were at particular risk. A high prevalence of emotional disturbance among health care practitioners is likely to compound existing problems of health care provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 23 publications
5
32
2
4
Order By: Relevance
“…This is consistent with the findings of Jafari et al; (15) but Sherina et al found no association between the years of study in medical school and mental health (7) neither Assadi et al found any significant difference between undergraduate students, interns and postgraduates. (18) Although mean GHQ scores were not significantly different in three groups of socioeconomic status, the participants with lowest economic position had higher scores. Assadi et al also reported this; (18) similarly, being from a non-poor family was considered as a factor helping better mental health status by Yang et al (23) However, socioeconomic status in our study was self-reported and only measured by family monthly income, which might not present the exact socioeconomic position of the participants.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…This is consistent with the findings of Jafari et al; (15) but Sherina et al found no association between the years of study in medical school and mental health (7) neither Assadi et al found any significant difference between undergraduate students, interns and postgraduates. (18) Although mean GHQ scores were not significantly different in three groups of socioeconomic status, the participants with lowest economic position had higher scores. Assadi et al also reported this; (18) similarly, being from a non-poor family was considered as a factor helping better mental health status by Yang et al (23) However, socioeconomic status in our study was self-reported and only measured by family monthly income, which might not present the exact socioeconomic position of the participants.…”
Section: Discussionmentioning
confidence: 82%
“…(18) Although mean GHQ scores were not significantly different in three groups of socioeconomic status, the participants with lowest economic position had higher scores. Assadi et al also reported this; (18) similarly, being from a non-poor family was considered as a factor helping better mental health status by Yang et al (23) However, socioeconomic status in our study was self-reported and only measured by family monthly income, which might not present the exact socioeconomic position of the participants.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations